Collapse of a nonductile concrete frame Evaluation of analytical models. - Yavari, Soheil (Earthquake engineering & structural dynamics.)
The current paper presents nonlinear dynamic analyses that simulate shaking table tests performed on a four-column reinforced concrete frame described in a companion paper. The frame consists of two ductile and two nonductile columns interconnected by a stiff beam. In order to validate existing analytical models for nonductile concrete columns, a blind comparison of the test data and results of the analysis is performed. The analysis adequately captures the drift response and correctly detects collapse of the structure; however, strength degradation due to cover spalling is exaggerated in the analytical model. Refinement of the analysis by changing the concrete cover model results in an excellent agreement between the test data and analysis results at the initiation of shear failure and collapse of the frame. The experimental data are further compared with lumped-plasticity nonlinear models used in engineering practice. The results suggest that the sudden strength degradation used in ASCE/SEI 41-06 results in an exaggerated estimate of the displacement demands. It is also observed that ignoring the strength degradation, using an elastic-perfectly-plastic model, provides a good estimate of the displacement demands when strength degradation is not severe.